Access Behaviour Capacity and Usage on Social Media: Exploring Higher Distance Education Students' Perception - Djoko Rahardjo; Arifah Bintarti (Jurnal ASPIKOM - Jurnal Ilmu Komunikasi, 2023)
The extensive usage of social media in today's globalized society has had an impact on the education industry. To undertake academic and non-academic activities, social media are usually utilized by students in higher distance education to communicate with peers and instructors during the learning process. Some of them had difficulty adjusting to the new method of learning. The goal of the study is to examine how they utilize social media in relation to their access behaviour. This online survey received responses from 549 individuals in purposive samplingThe finding shows a considerable correlation between access capacity behaviour and social media usage. It is evident that access habits, which are supported by behaviour and accessibility, have a substantial effect on the use of entertainment and socialization. Based on these findings, it is understandable that social media offer more abundantly relaxing contents that easily tempts students than the serious ones. In order to address this issue, educational institutions must develop several easy and engaging media-based educational tools.